Protein requirements for growth in male and female Saanen goats - Almeida, Amelia Katiane de [UNESP]; Resende, Kleber Tomas de [UNESP]; Silva, Simone Pedro da; Soares, Diogo da Costa [UNESP]; Machado da Rocha Fernandes, Marcia Helena [UNESP]; Molina de Almeida Teixeira, Izabelle Auxiliadora [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
The objective of this study was to determine the protein requirements for the growth of intact male, female, and castrated male Saanen goats weighing 30 to 45 kg of body weight (BW) and to compare estimates of the protein requirements for maintenance (NPm) by the comparative slaughter and nitrogen balance techniques. To determine the maintenance requirements, 55 goats were assigned in a split-plot design using a 3 x 3 factorial arrangement (three sexes and three dry matter intake (DMI) levels). A linear regression of retained N (as measured by the slaughter technique and estimated from the nitrogen balance) on N intake on a daily basis was used to calculate the net protein for maintenance. The net protein requirement for weight gain (NPg) was obtained using 65 goats fed ad libitum in a completely randomized design. The first derivative of the allometric equation of protein content in the empty BW with respect to the empty BW yielded estimates of the NPg. According to the comparative slaughter technique, the estimated NPm was 1.46 g/kg of metabolic weight, which is 50% lower than the estimate from the nitrogen balance technique. When evaluating the variance of the error, the nitrogen balance also showed greater values, indicating less precision compared with that of the comparative slaughter technique. The daily NPg ranged from 155.7 +/- 10.9 to 153.4 +/- 13.5 g/kg of EBW gain for growing Saanen goats. The protein requirements (NPm and NPg) of intact male, female, and castrated male Saanen goats are similar, from 30 to 45 kg BW, in accordance with current feeding systems. Moreover, the results of the present study indicate that the estimate of NPm using the comparative slaughter technique is more precise and lower than that using the N balance technique.
Keywords: comparative slaughter; dairy; factorial approach; maintenance; nitrogen balance